Agrotech Ecosystems: Towards an Analysis of Capabilities and Innovation Outcomes in R (Global Journal of Science Frontier Research, 2024)
The growing global demand for food coupled with the challenges posed by conventional production methods to sustainability as well as the emphasis on value addition at the source and differentiation make it imperative to incorporate new technologies into agricultural enterprises These new technologies known as Industry 4 0 technologies are giving rise to the AgTech phenomenon by expanding capabilities There are regions where technology hubs or parks are situated featuring the presence of large companies as well as technological small and medium-sized enterprises SMEs research and development R D centers and extension and transfer institutions indicating the existence of ecosystems coexisting with other actors in the pursuit of agro-oriented innovations This study is part of a broader research initiative aimed at mapping the supply and demand for technology within the AgTech Ecosystem and identifying the degree of alignment between supply and demand in the influence region of the National University of the Center of the Province of Buenos Aires UNICEN As a result the expectation is to develop a prototype of a georeferenced online platform that integrates information from various actors and provides a measure of how aligned or misaligned the technological supply and demand are
Keywords: capabilities - innovation - R